Colonial origins of the resource curse: endogenous sovereignty and authoritarianism in Brunei. Issue 2 (17th February 2020) - Mukoyama, Naosuke
ABSTRACT: The literature on the political "resource curse" has recently seen heated debates over the average causal effects of oil on democracy and the generalizability of the theory. One of the reasons these disagreements remain unresolved is that the causal mechanisms of the resource curse receive little scholarly attention and historical and international aspects are frequently overlooked. To address these problems, this study investigates the relationship between oil and the political regime in Brunei, arguably the most understudied state among the archetypes of the resource curse, extending the time frame back to the very beginning of oil exploration during the colonial period. It uncovers a previously overlooked causal process by which oil affected the emergence of authoritarianism. It shows that in the case of Brunei (and potentially some Persian Gulf monarchies), sovereignty is endogenous to the resource curse. That is, oil, together with indirect colonial rule, affected the creation of the state, and this state-formation process contributed to the long-standing autocracy. This study contributes to the resource curse literature by identifying a new mechanism of the resource curse, showing that we need to reconsider the way we apply the potential outcomes approach, and highlighting the importance of historical and international factors.